Metaphors of War in Effective and Ineffective Coping of Medical Directors of COVID-19 Wards in Public Hospitals - Naamati-Schneider, Lior; Gabay, Gillie (Frontiers in Public Health, 2022)
The COVID-19 pandemic has challenged medical professionals worldwide with an unprecedented need to provide care under conditions of complexity, uncertainty, and danger. These conditions, coupled with the unrelenting stress of overwhelming workload, exhaustion, and decision-making fatigue, have forced clinicians to generate coping mechanisms. This qualitative study explored the use of metaphors as a coping mechanism by clinical directors of COVID-19 divisions in Israeli public general hospitals while they were exposed to death and continuous trauma throughout the outbreak of the pandemic and its first wave (March to June 2020). The study employs discourse methodology and metaphor mapping analysis to capture the personal, organizational, and social dimensions of the processes of effective and ineffective coping with an extreme health crisis. Analysis revealed that the metaphors that clinical directors used reflect a dual process of mediating and generating the social construction of meaning and facilitating effective and ineffective coping. Effective coping was facilitated by war metaphors that created a sense of mission and meaningfulness at both the organizational and the individual levels. War metaphors that generated a sense of isolation and sacrifice intensified helplessness and fear undermined coping. We propose actionable recommendations to enhance effective coping for individuals and organizations in this ongoing pandemic.